The Cambridge handbook of privatization - Dorfman, Avihay (Cambridge law handbooks, 2021)
"The outcome-based approach assesses the privatization of the provision of a good or a service by reference to the quality or quantity of its provision. Private provision is desirable when private entities make better - more efficient, just, etc.- decisions with respect to the relevant good/service than public entities. The most influential outcome-based approach is the economic theory which typically considers the merits of privatization on efficiency-based grounds. Alternatively, it can be argued that public entities have valuable process-related properties; for instance, public institutions, are more accountable, transparent, and answerable to their beneficiaries and other constituents. A process-based approach focuses its attention on the decisionmaking procedures, in particular, the reasoning of the institution rather than on outcomes. Finally, some theorists maintain that the identity of the agent itself may matter. For instance, it is claimed that being a private or a public entity is crucial for the very possibility of engaging in certain enterprises, e.g., legislation or the imposition of criminal punishment as these are agent-dependent practices; their success hinges on the identity of the agent"--